Microhabitats and oribatid fauna: comparison of 2 sampling approaches - Skubała, Piotr (Biological Letters, 2017)
Oribatid fauna highly varies among habitats, but different microhabitats within a habitat are also characterized by different mite species. The main goal of the research was to compare the observed structure of an oribatid community when samples were collected at random from the soil-litter layer of 0-10 cm in depth (standard approach) and selectively from 6 types of available microhabitats (complex approach). Samples were taken within a small plot (10 m × 10 m) in a forested area of the Silesian Park (Chorzów, south Poland). Overall, 2642 specimens of Oribatida belonging to 62 species were collected in 66 samples. The structure of the oribatid community observed by means of the 2 sampling approaches was completely different. The abundance and species richness of oribatid mites collected from 6 microhabitats were significantly higher than in the soil-litter layer alone. Results of this study show that random collecting of only soil-litter samples may reduce the evaluation of species richness in a study area by 40%. Each of the studied microhabitats supported a peculiar oribatid fauna.